Risk factors associated with the development of elimination stoma and peristomal skincomplications - Pinto, Igor (2017)
Background: Stoma formation leads to changes that are influenced by several factors, namely the presence of stoma and/or peristomal skin complications. It is estimated that 80% of ostomy patients have at least one stoma-related complication throughout their life. Objectives: To identify the risk factors associated with the development of elimination stoma and peristomal skin complications. Methodology: Literature review, based on the methodological strategy of the Joanna Briggs Institute for scoping reviews. A total of 1,492 articles were identified, of which 22 were included for analysis. Results: Most of the risk factors for the development of complications are non-modifiable. Pre and postoperative education, stoma site marking, and follow-up after hospital discharge are some of the nursing-sensitive factors. Conclusion: The identification of risk factors associated with the development of stoma complications allows nurses to early identify patients’ vulnerability indicators and intervene more effectively.